Suicidal Ideation Mediates the Relationship Between Affect and Suicide Attempt in Adolescents - Rubio, Andrés; Oyanedel, Juan Carlos; Bilbao, Marian; Mendiburo-Seguel, Andrés; López, Verónica; Páez, Dario (Frontiers in Psychology, 2020)
Suicide, as one of the leading causes of death for the adolescent population, both in Chile and globally, remains a complex and elusive phenomenon This research studies the association between positive and negative affect in relation with suicidal ideation and suicidal attempt, given that affectivity is a fundamental basis on which people make evaluations on their satisfaction with life. First, it examines the reliability, structure, and validity of Watson's PANAS scale in a representative random sample of Chilean high school students (N = 4,568). The scale evidences strong reliability coefficients and a confirmatory factor analysis, excluding one positive (excited) and one negative (nervous) item. The scale shows a satisfactory goodness of fit. Secondly, it investigates the association of PANAS positive and negative affect scores with suicidal ideation as well as reported attempt in adolescents, controlling for the potential effect of age and sex (N = 420 high school students). Low positive and high negative affect, but not sex and age, show a significant association with suicidal ideation. Suicidal ideation totally mediates the association of affect with suicide attempt, as expected. Results are discussed regarding prevention and it considers how positive and negative affect can be relevant as indicators for prevention and treatment using widely available technology.